2021
DOI: 10.1002/adem.202100978
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight and Highly Heat‐Resistant Microcellular Polyetherimide/Barium Titanate/Carbon Nanotube Nanocomposites with High Dielectric Permittivity and Low Dielectric Loss

Abstract: Dielectric materials can be used to control/ store charge and electric energy, which has important potential application value for the dielectric energy storage and intelligent sensing in areas such as aerospace, electronics, and military engineering. [1,2] The dielectric materials with high dielectric permittivity (ε 0 ) and low dielectric loss (tanδ) are of great significance to national security defense and economic development. [3][4][5][6] Ceramic-based dielectric materials are widely used in electronic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…However, with the increase of filler content, ZIF‐67 reduces the van der Waals force between molecular chains, and the plasticizing effect on the composite material becomes more and more obvious, thereby reducing T g . [ 44 ] When the ZIF 8–67 content was 0.5 wt%, the T g of the nanocomposite was the highest (263.87 °C). The above results also indicated that the appropriate amount of ZIF 8–67 could help to improve the temperature stability of the nanocomposites.…”
Section: Resultsmentioning
confidence: 99%
“…However, with the increase of filler content, ZIF‐67 reduces the van der Waals force between molecular chains, and the plasticizing effect on the composite material becomes more and more obvious, thereby reducing T g . [ 44 ] When the ZIF 8–67 content was 0.5 wt%, the T g of the nanocomposite was the highest (263.87 °C). The above results also indicated that the appropriate amount of ZIF 8–67 could help to improve the temperature stability of the nanocomposites.…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, the introduction of nano fillers will lead to volume exclusion, which will increase the free volume between molecular chains. On the other hand, if the nano filler has a good interfacial bonding with the molecular chain, it can act as cross‐linking point, so as to limit the movement of the molecular chain and improve the glass transition temperature 33 . It is indicated that MXene@CTAB has good interaction with polyimide molecules and further improves the service temperature of the nanocomposites.…”
Section: Resultsmentioning
confidence: 99%
“…To address this issue, much research has been conducted from the perspective of interfacial control. The introduction of core–shell structured nanoparticles has been demonstrated to be a viable method, such as BTO@SiO 2 , 15–17 BTO@Al 2 O 3 , 18,19 BTO@TiO 2 , 20–23 SiO 2 @PVDF, 24 BTO@PDA, 25–29 and dopamine@BCZT, 30,31 BTO@TiO 2 /P(VDF-HFP) nanocomposites reported by Nan et al 9 achieved a high U e of 31.2 J cm −3 , which was nearly 15 times as large as that of BOPP. The local electric field concentration and carrier accumulation were suppressed by introducing TiO 2 with a moderate ε r (∼40), achieving the purpose of simultaneously increasing polarization and E b .…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism is that the charge transfer path is optimized by the insulating shell, which can confine the carriers in the insulating shell layer, making it difficult to form the leakage current and conducting channel. 15,24,25 However, U e of nanocomposites cannot be effectively improved to a large extent due to the low polarization of most insulating shells, such as PVDF and PDA. The enhancement of the polarization and the control of the charge transfer path through reasonable interface design to improve the U e and η have become key problems to be solved.…”
Section: Introductionmentioning
confidence: 99%